2018
DOI: 10.3390/rs10091451
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the L-Band Snow-Covered Surface Emission in a Winter Canadian Prairie Environment

Abstract: Detailed angular ground-based L-band brightness temperature (TB) measurements over snow covered frozen soil in a prairie environment were used to parameterize and evaluate an electromagnetic model, the Wave Approach for LOw-frequency MIcrowave emission in Snow (WALOMIS), for seasonal snow. WALOMIS, initially developed for Antarctic applications, was extended with a soil interface model. A Gaussian noise on snow layer thickness was implemented to account for natural variability and thus improve the TB simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It also enables measurements of layer boundary roughness, particularly of the snowair and snow-ground interfaces. Other methods to characterize snow-air surface roughness use photographic image contrast analysis of dark boards placed behind snow (Fassnacht et al, 2009;Anttila et al, 2014) and subnivean roughness of areas cleared of snow using pin profilers, lidar scanning (Chabot et al, 2018;Roy et al, 2018), or structure from motion photogrammetry (Meloche et al, 2020). The subnivean roughness between snow and soil gives significant contributions of rough surface scattering because of the contrast of dielectric constants between snow and soil.…”
Section: Planning a Satellite Missionmentioning
confidence: 99%
“…It also enables measurements of layer boundary roughness, particularly of the snowair and snow-ground interfaces. Other methods to characterize snow-air surface roughness use photographic image contrast analysis of dark boards placed behind snow (Fassnacht et al, 2009;Anttila et al, 2014) and subnivean roughness of areas cleared of snow using pin profilers, lidar scanning (Chabot et al, 2018;Roy et al, 2018), or structure from motion photogrammetry (Meloche et al, 2020). The subnivean roughness between snow and soil gives significant contributions of rough surface scattering because of the contrast of dielectric constants between snow and soil.…”
Section: Planning a Satellite Missionmentioning
confidence: 99%
“…It also enables measurements of layer boundary roughness, particularly of the snow-air and snow-ground interfaces. Other methods to characterise snow-air surface roughness use photographic image contrast analysis of dark boards placed behind snow (Fassnacht et al, 2009;Anttila et al, 2014) and subnivean roughness of areas cleared of snow using pin profilers, LiDAR scanning (Chabot et al, 2018;Roy et al, 2018) or structure from motion photogrammetry (Meloche et al, 2020). The subnivean roughness between snow and soil give significant contributions of rough surface scattering because of the contrast of dielectric constants between snow and soil.…”
Section: Spatial Variability Of Field Measurementsmentioning
confidence: 99%
“…Leduc-Leballeur et al [10] proposed the wave approach for low-frequency microwave emission in snow (WALOMIS) model, and experiments in Antarctica showed that the wave approach was more suitable than the radiative transfer model to simulate the L-band TB. Roy et al [11] applied WALOMIS to snow in a prairie environment and compared it with the DMRT-ML and LS-MEMLS-1L models for L-band TB simulation, and the results showed that the root-mean-square errors of the three model simulations were similar at about 7.2~10.5 k.…”
Section: Introductionmentioning
confidence: 99%